Direct Detection of Fungal Siderophores on Bats with White-Nose Syndrome via Fluorescence Microscopy-Guided Ambient Ionization Mass Spectrometry - Mascuch, Samantha J.; Moree, Wilna J.; Hsu, Cheng-Chih; Turner, Gregory G.; Cheng, Tina L.; Blehert, David S.; Kilpatrick, A. Marm; Frick, Winifred F.; Meehan, Michael J.; Dorrestein, Pieter C.; Gerwick, Lena (PLOS ONE, 2015)
White-nose syndrome (WNS) caused by the pathogenic fungus Pseudogymnoascus destructans is decimating the populations of several hibernating North American bat species. Little is known about the molecular interplay between pathogen and host in this disease. Fluorescence microscopy ambient ionization mass spectrometry was used to generate metabolic profiles from the wings of both healthy and diseased bats of the genus Myotis. Fungal siderophores, molecules that scavenge iron from the environment, were detected on the wings of bats with WNS, but not on healthy bats. This work is among the first examples in which microbial molecules are directly detected from an infected host and highlights the ability of atmospheric ionization methodologies to provide direct molecular insight into infection.